Assessment of Health-Related Quality of Life among People Living with HIV in Xinjiang, West China. (November 2017) - Maimaiti, Rena; Yuexin, Zhang; Kejun, Pan; Wubili, Maimaitaili; Lalanne, Christophe; Duracinsky, Martin; Andersson, Rune
In total, 679 HIV-positive patients from 4 clinics in Urumqi city were given structured questionnaires by the doctors or nurses treating them. Health-related quality of life (HRQL) was assessed using the Chinese Patient-Reported Outcome Quality of Life-HIV questionnaire versions in Mandarin and Uyghur. This tool has been used in other parts of China and several countries. Compared to France, Australia, United States, Brazil, Thailand, Cambodia, Senegal, and Central-Southern China (CS China), the HRQL was significantly lower among HIV-positive patients in Xinjiang, with regard to the dimension of treatment impact and general health score. The health concern was similar to Brazil and Cambodia but lower than other countries and CS China. Our findings showed high stigmatization: 86% of the patients were afraid to tell others they were HIV positive and 69% often felt or always felt depressed. Only 1% of the patients were on antidepressant treatment.